How Oxidation and Dissolution in Diabase and Granite Control Porosity during Weathering. Issue 1 (14th November 2014) - Bazilevskaya, Ekaterina; Rother, Gernot; Mildner, David F.R.; Pavich, Milan; Cole, David; Bhatt, Maya P.; Jin, Lixin; Steefel, Carl I.; Brantley, Susan L.
Abstract : Weathering extends to shallower depths on diabase than granite ridgetops despite similar climate and geomorphological regimes of denudation in the Virginia (United States) Piedmont. Deeper weathering has been attributed to advective transport of solutes in granitic rock compared to diffusive transport in diabase. We use neutron scattering (NS) techniques to quantify the total and connected submillimeter porosity (nominal diameters between 1 nm and 10 μm) and specific surface area (SSA) during weathering. The internal surface of each unweathered rock is characterized as both a mass fractal and a surface fractal. The mass fractal describes the distribution of pores (∼300 nm to ∼5 μm) along grain boundaries and triple junctions. The surface fractal is interpreted as the distribution of smaller features (1–300 nm), that is, the bumps (or irregularities) at the grain–pore interface. The earliest porosity development in the granite is driven by microfracturing of biotite, which leads to the introduction of fluids that initiate dissolution of other silicates. Once plagioclase weathering begins, porosity increases significantly and the mass + surface fractal typical for unweathered granite transforms to a surface fractal as infiltration of fluids continues. In contrast, the mass + surface fractal does not transform to a surface fractal during weathering of the diabase, perhaps consistent with the interpretation that solute transport is dominated by diffusion in that rock. The difference in regolith thickness between granite and diabase is likely due to the different mechanisms of solute transport across the primary silicate reaction front.